ATTITUDES AND DRIVING BEHAVIOR FACTORS ON THE TRAFFIC ACCIDENTS AMOUNG YOUNG MOTORCYCLIST IN SURABAYA CITY - Dimas Puji Santosa; Hera Widyastuti (Journal of Civil Engineering, 2022)
The majority of traffic accidents in Surabaya are dominated by motorcycles and drivers which whom mostly were teenagers This study aims to examine the relationship between attitudes, driving behavior, and traffic accidents among young motorcyclist in Surabaya. The study used a primary dataset of 435 motorcyclists from 17to 25-year-old. This study uses a structural equation modelling approach to determine the relationship between attitudes towards risky driving behavior, driving behavior, and traffic accidents. The driving behavior parameters used are divided into six parameters: traffic errors, speed violations, control errors, traffic violations, safety violations, and stunts. The results of this study indicate that all driving behavior parameters are significantly influenced by the driver's attitude towards risky driving behavior. In which the parameters that have a significant effect on traffic accidents are traffic errors and traffic violations.